Vaccine research and development (R&D) in the Asia-Pacific: The economics of vaccine R&D and policy recommendations to overcome market failures and promote R&D cooperation - Antonio Postigo (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2022)
The COVID-19 pandemic has highlighted both the strengths and weaknesses of national, regional, and global vaccine research and development (R&D) systems. Translating public and private R&D efforts into effective vaccines in a timely manner requires not only sufficient financial and scientific resources but also a policy-driven R&D ecosystem that fosters innovation, public-private partnerships, and international cooperation. This paper outlines several supply-side and demand-side factors behind vaccine R&D that generate economic disincentives for pharmaceutical firms to invest in vaccine R&D and can lead to a market failure for vaccines targeting diseases in low-income countries. Most developing countries in Asia-Pacific not only lack the financial and technological resources to invest in vaccine R&D, but it is also not sensible to develop and replicate R&D capabilities in each country. Consequently, low-income countries are dependent on vaccines researched, developed, and manufactured by other nations that they must obtain through trade and international cooperation. The Asia-Pacific region accounts for the largest share of global R&D spending and large shares in publications and patents on vaccine R&D. The region is home to dozens of state-owned and private pharmaceutical firms and contract research organizations that conduct vaccine R&D. Global pharmaceutical firms have not only offshored part of their vaccine manufacturing to Asia-Pacific but also transferred some of their R&D activities. Countries in Asia-Pacific have used several supply-side and demand-side approaches to incentivize investments in vaccine R&D. For instance, high-income countries are major contributors to product development partnerships and philanthropic foundations and have launched programs to boost university-industry R&D ties. During the COVID-19 pandemic, many high- and middle-income countries in the region established advanced market commitments for vaccine doses. The COVID-19 pandemic also showed the possibilities and challenges of international cooperation in vaccine R&D. Pharmaceutical firms in some developing countries built their vaccine R&D capabilities through technological transfer from highincome countries. Regional institutions and intergovernmental organizations in AsiaPacific have also helped promote and coordinate regional cooperation in vaccine R&D. This paper proposes policy actions to stimulate investments in vaccine R&D and promote regional cooperation along four dimensions, namely a) on the prioritization of targets in the vaccine R&D pipeline; b) on how to overcome market failures in vaccine R&D; c) on fostering partnerships between relevant stakeholders at the national and regional levels; and d) on increasing the preparedness and response of national and regional vaccine R&D systems.
Keywords: F15; F21; I18; 330; COVID-19; vaccines; medical products; R&D; regional cooperation; Asia-Pacific